2009
DOI: 10.1111/j.1365-3016.2009.01060.x
|View full text |Cite
|
Sign up to set email alerts
|

Children with cerebral palsy: severity and trends over time

Abstract: Increasingly, more very-low-birthweight infants in the developed world are now expected to survive the neonatal period than was previously the case. There are concerns that there may be a related increase in the number of infants developing severe sensorimotor impairments. Pooled data from five registers contributing to the UK Network of Cerebral Palsy Registers, Surveys and Databases were used to identify patterns of motor impairment in relation to additional impairments and to birthweight, and to assess whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
44
2
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 23 publications
3
44
2
2
Order By: Relevance
“…[5] Less research has been carried out on the epidemiology of CP in children of NBW than in those of very low birthweight (< 1500 g). As the number and severity of impairments increase with increasing gestational age [6,7] and birthweight, [8] the type of brain lesion among term or NBW children tends to exhibit a different pattern to that of preterm or low birthweight births. [9][10][11] Time trends for CP prevalence in NBW children vary across studies.…”
Section: Introductionmentioning
confidence: 99%
“…[5] Less research has been carried out on the epidemiology of CP in children of NBW than in those of very low birthweight (< 1500 g). As the number and severity of impairments increase with increasing gestational age [6,7] and birthweight, [8] the type of brain lesion among term or NBW children tends to exhibit a different pattern to that of preterm or low birthweight births. [9][10][11] Time trends for CP prevalence in NBW children vary across studies.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Surman et al [18] showed that individuals with higher birth weight developed CP in the most severe form.…”
Section: Discussionmentioning
confidence: 89%
“…La enfermedad discapacitante más frecuente de nuestro Instituto es la PC, lo que se ajusta a la realidad mundial, pues es la principal causa única de discapacidad física en la población infantil global 20,21 . La PC constituye un síndrome y se define como una lesión o anormalidad no progresiva que se produce en un cerebro en desarrollo y que lleva a una alteración permanente en la esfera motora o del movimiento 22 .…”
Section: Discusión Y Conclusionesunclassified